HPV16-L1-specific antibody response is associated with clinical remission of high-risk HPV-positive early dysplastic lesions - Mehlhorn, Grit; Hautmann, Simone K.; Koch, Martin; Strehl, Johanna D.; Hartmann, Arndt; Hilfrich, Ralf; Beckmann, Matthias; Griesser, Henrik (Anticancer Research, 2014)
The present study was aimed at clarifying if use of a rapid human papillomavirus type 16 L1-specific antibody test could be used to improve clinical management of high-risk HPV-positive low-grade squamous intraepithelial lesion (LSIL)/high-grade squamous intraepithelial lesion (HSIL).The study was nested within a prospective study of 801 patients with early dysplastic high-risk HPV-positive lesions to examine the prognostic significance of HPV-L1 protein detection. Serum samples of 87 patients were tested with a rapid HPV16-L1-specific antibody test. The results were correlated with the clinical outcome during 66 months of follow-up.A combined analysis of the 22 antibody-positive women showed that 17 were also L1 protein-positive, and 5 were L1 capsid protein-negative. An HPV-specific immune competence strongly correlates with clinical remission of low-grade squamous intraepithelial lesion (76.6%). For L1 antigen and HPV16-L1 antibody double-positive women, the risk of progression to cervical intraepithelial neoplasia grade 3 was low (5.8%).The rapid anti-HPV16-L1 test could be a promising tool to improve risk assessment and appropriate clinical management of high-risk HPV-positive early dysplastic lesions.
EVALuna2:6623